(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Rohinton Mistry’s novels reflect interest in the importance of personal and cultural identity. It is obvious that Mistry has well depicted his deep attachment and nostalgia for his homeland. The social and cultural nostalgia helped him to create a sense of loss. He recognizes the consequence of religion and rite in the construction of human identity. Rohinton Mistry is an expatriate Indian-Parsi writer who lives in Canada. As a Parsi and also a immigrant in Canada, he look at him as a symbol of double displacement and this sense of displacement is a recurrent theme in his literary works. His historical situation includes development of new identity in the nation to which he has migrated and a complex relationship with political and cultural history of the nation he has left behind.